The wavelength conversion in WDM networks - Miroslav Bahleda; Karol Blunar (Communications - Scientific letters of the University of Zilina, 2004)
In this paper we deal with the problem of wavelength conversion in WDM (wavelength division multiplex) networks. In all-optical networks the data are transmitted through optical networks transparently. It means that the data still remain in the optical domain between the source and end node. The data transmission between two nodes can be without wavelength conversion or with wavelength conversion (with full wavelength conversion or limited wavelength conversion). We want to give a comprehensive paper about recent and new forms of wavelength conversion.